DEVELOPMENT OF PARTICIPATORY NETWORK ADMINISTRATION OF ROYAL THE AWARDED BUDDHIST ORIENTED SCHOOLS - Rattanosopha, Ratee; Srivichai, Suddhipong; Thitavaddhano, Phramaha Yannawat (Journal of Educational Review Faculty of Education in MCU, 2021)
The objectives of this research articles were to propose the development of Participatory Network Administration of the Royal Awarded Buddhist Oriented Schools. The mixed research method was used in the study. The research procedure was divided into 3 steps which were (1) to study the state of Participatory Network Administration of the Royal Awarded Buddhist Oriented Schools from 176 samples by using questionnaires and analyzed by percentage, mean and standard deviation; (2) to develop the Participatory Network Administration by structured in-depth interviews with 9 key informants and analyzed by content analysis; and (3) to propose the development of Participatory Network Administration of the Royal Awarded Buddhist Oriented Schools by focus group discussion with 9 experts and analyzed by content analysis. Results of the study found that the development of Participatory Network Administration of the Royal Awarded Buddhist Oriented Schools consisted of 6 main principles; (1) co-objective integrated with being endowed with right views along with one’s fellows, (2) member participation integrated with keeping without blemish the rules of conduct along with one’s fellows, (3) co-administration integrated with sharing any lawful gains with virtuous fellows, (4) co-learning integrated with being amiable in thought, (5) co-communication development integrated with being amiable in word, and (6) participation in network extension integrated with being amiable in deed.